2020
DOI: 10.1142/s136391962150033x
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation and New Product Success Relationship: The Role of Innovation Capability, Absorptive Capacity, Green Brand Positioning

Abstract: We explored the mediating role of innovation capability in the relationship between market orientation and new product success; the moderating role of realised absorptive capacity in the relationship between market orientation and innovation capability; and finally, the moderating role of green brand positioning in the relationship between innovation capability and new product success. Empirical analysis was based on 329 manufacturing firms. Various validity and reliability checks were conducted before the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 94 publications
0
26
0
Order By: Relevance
“…From Table 3, the least √AVE was 0.709, which the highest correlation coefficient was 0.606, which suggests discriminant was achieved by this study. Since the highest correlation coefficient was also less than 0.7, it was concluded that there was no multicollinearity which could potentially cause any confounding effects in the model estimation (Dogbe et al, 2021).…”
Section: Convergent Validity Was Assessed Using Average Variance Extr...mentioning
confidence: 99%
“…From Table 3, the least √AVE was 0.709, which the highest correlation coefficient was 0.606, which suggests discriminant was achieved by this study. Since the highest correlation coefficient was also less than 0.7, it was concluded that there was no multicollinearity which could potentially cause any confounding effects in the model estimation (Dogbe et al, 2021).…”
Section: Convergent Validity Was Assessed Using Average Variance Extr...mentioning
confidence: 99%
“…The first company has 5 departments, which were the Marketing department, Finance department, Quality department, Safety department, Security department with 150 employees while the second company has 5 department Similar to Everpure Drinking Water Ltd, with 100 employees. The researcher used purposive sampling in selecting key informants who were vested in knowledge on the subject matter researched (Dogbe et al, 2021). The sample size for the survey was 250 out of population of 670 employees from the two Sachet water company.…”
Section: Collecting Datamentioning
confidence: 99%
“…Market orientation had three sub-dimensions, which were customer orientation (4 items), inter-functional coordination (5 items), and competitor orientation (4 items). The measurement items under customer orientation were adapted from Dogbe et al (2020a). Absorptive capacity also had 4 sub-dimensions, which were acquisition (6 items), transformation (6 items), assimilation (3 items), and exploitation (6 items).…”
Section: Measurement Of Variablesmentioning
confidence: 99%